Status of LHC Searches for SUSY without R-Parity - Roberto Franceschini (Advances in High Energy Physics)
In this contribution we briefly review the status of current searches for supersymmetry at the Large Hadron Collider, focusing especially on viable sub-TeV colored superpartners which can appear in nonstandard scenarios. The presented material covers mostly signals that do not crucially rely on the presence of large missing transverse momentum, with special emphasis on R-parity violating supersymmetry. For some scenarios the prospects for the next run of the Large Hadron Collider and future machines are also presented.